EVALUATION OF PASSENGER SERVICE ON KMP.SENANGIN ON THE KUALA TUNGKAL – DABO SINGKEP LINE - Pujianto, Erli; Ulya, Febriyanti Himmatul; Daffa, Muhammad (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2025)
Kuala Tungkal Ferry Port is located in West Tanjung Jabung Regency, Jambi Province. Kuala Tungkal Ferry Port has four operating ships: KMP.Sembilang, KMP.Citra Nusantara, KMP.Satria Pratama, and KMP. Senangin. KMP. Senangin is the only ship operating on the Kuala Tungkal – Dabo Singkep route. Several services are not in accordance with regulations and are carried out by ship operators, even though services on board have been regulated by the government to provide a sense of safety and comfort during the crossing. This study aims to determine the level of conformity of passenger services on KMP Senangin with the current Minimum Service Standards and to determine the level of user satisfaction with KMP Senangin passenger service facilities. The method used is an analysis of the level of conformity of the Minimum Service Standards for ferry transportation andCustomer Satisfaction Index(CSI)To determine the level of satisfaction of service users with the current passenger service facilities, the analysis and calculations showed that KMP.Senangin had a level of suitability for passenger services of 77.4%, and a service user satisfaction score of 64.17%..